"We're all thrown in the same boat … ": A qualitative analysis of peer support in dementia care. (July 2016) - Keyes, Sarah E; Clarke, Charlotte L; Wilkinson, Heather; Alexjuk, Eva Joanna; Wilcockson, Jane; Robinson, Louise; Reynolds, Joanna; McClelland, Siobhan; Corner, Lynne; Cattan, Mima
Peer support is well established in fields such as the disability movement and mental health and is increasingly recognised as one way of enabling support by and for people with a diagnosis of dementia and their immediate carers. It was central to the implementation of the National Dementia Strategy (NDS) for England, when 40 demonstration sites were established. This mixed-methods study included in-depth qualitative interviews with people living with dementia ( n = 101) and staff/stakeholders ( n = 82) at 8 of the 40 sites. Data analysis was a five-stage process: coding framework developed (using 25 transcripts); further development of the framework (using a further 70 transcripts); development of emerging themes; modelling of themes and verification of models based on the entire data set. Peer support had positive emotional and social impact that was rooted in identification with others, a commonality of experience and reciprocity of support. There was also a contrast between the quality of peer support and support from professionals. This emphasises the significance of lived experience and promoting a strength-based approach to interpersonal support that is enabling and challenges a deficit approach to understanding dementia.